Evaluasi Desain Squeeze Cementing Pada Sumur “TOKAI” Lapangan “PALMA” Menggunakan Metode Bradenhead - Ansek, Inggrid Angelina; Septiani, Septiani; Hutabarat, Romauli Tiurma (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Squeeze cementing is a secondary cementing method used to overcome loss circulation problems and improve well integrity. This study aims to evaluate the squeeze cementing design in the “TOKAI” well, “PALMA” field using the bradenhead method. The methodology includes well data analysis, cement slurry requirement calculations, and evaluation of job performance based on pressure testing. The bradenhead method was selected due to its operational simplicity and because it does not require a packer. The calculation results indicate that 44 sacks of cement are required to produce 9.02 bbl of slurry, including a 2 bbl squeeze volume. The evaluation shows that the squeeze cementing operation was successful, indicated by a stable positive pressure test and the presence of fluid return. This method is proven effective in isolating perforation zones experiencing loss circulation.